FORECASTING THE PROCESS OF SCIENTIFIC CREATIVITY IN LAW (World Bulletin of Management and Law, 2025)
The article discusses the theoretical and practical aspects of forecasting the process of scientific creativity in law. Particular attention is paid to the patterns of formation of scientific ideas, stages of scientific research and innovative thinking in legal science. The author analyzes the role of predictive methods in the development of legal research, emphasizing the importance of a systematic approach to the formation of future legal concepts. The mechanisms for stimulating the scientific potential of young lawyers and the importance of interdisciplinary connections in legal creativity are also considered. The results of the study can be used in scientific and pedagogical activities, as well as in strategic planning for the development of legal science
Keywords: scientific creativity; jurisprudence; forecasting